Physiologic and molecular response of Fusarium oxysporum f. sp. zingiberi to ginger autotoxins - Yan Zhang; Hongshen Guo; Yanping Xu; Xiaochuan Chen; Miaomiao Zhang; Naicheng Li; Abdullah Gera (PLoS ONE, 2026)
Long-term monoculture of ginger triggers Fusarium wilt, a disease caused by Fusarium oxysporum f. sp. zingiberi ( Foz ). However, the interaction between autotoxins and pathogens remains poorly understood. This study examined the allelopathic effects of four autotoxins, syringic acid, coumarin, ferulic acid, and 7-hydroxycoumarin, on the growth, reproduction, and virulence traits of Foz . These compounds were previously identified as inhibitors of ginger growth and enzyme activity. The results revealed that the responses of Foz varied, likely because of the structural differences among the autotoxins. Syringic acid significantly inhibited mycelial growth, sporulation, and spore germination, while markedly enhancing the activity of cell wall-degrading enzymes and mycotoxin synthesis, as evidenced by the upregulation of FUB3 and FUB9 . Coumarin demonstrated a pronounced inhibitory effect on biomass production while concurrently stimulating sporulation and mycotoxin synthesis, as indicated by the upregulation of FUB6 and FUB9 . Ferulic acid treatment reduced the activity of cell wall-degrading enzymes and spore germination, while upregulating sporulation and mycotoxin synthesis. A similar pattern was observed with 7-hydroxycoumarin, which exerted a strong inhibitory effect on mycelial growth, biomass production, mycotoxin synthesis, and FUB gene cluster expression, except for FUB1 and FUB3 expression. In conclusion, four autotoxins exhibited diverse defensive roles against Fusarium wilt, whereas the pathogen enhanced its pathogenicity to counter host regulations. This study provides the first evidence of an interaction between ginger autotoxins and Foz .